Thailand : Investment Climate Assessment Update - World Bank (Washington, DC, 2012)
This report provides an up-to-date assessment of the investment climate of Thailand. As the socio-economic framework in which enterprises operate including infrastructure, policies and regulations improving the investment climate is helpful for productivity and economic growth. The report is based mainly on the results of the second round of the Thailand Productivity and Investment Climate Surveys (PICS) carried out in 2007 and on a comparison with results from the first round (conducted between March 2004 and February 2005). Some 1043 establishments from nine manufacturing sectors (food processing, textiles, garments, automobile parts, electronic parts, electrical appliances, rubber/plastics, furniture/wood, and machinery) in six regions (North, Central, metropolitan Bangkok, East, Northeast, and South) were surveyed. This report aims to present policymakers with detailed information on key business climate indicators and their relationship to Thai economic performance. Thailand's rapid growth and transition to middle-income country status in the past two decades was mainly the result of the rapid increase in employment and capital goods.